2009
DOI: 10.1016/j.neuron.2009.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Sound Localization in Reverberant Environments Is Mediated by Robust Encoding of Spatial Cues in the Auditory Midbrain

Abstract: In reverberant environments, acoustic reflections interfere with the direct sound arriving at a listener’s ears, distorting the spatial cues for sound localization. Yet, human listeners have little difficulty localizing sounds in most settings. Because reverberant energy builds up over time, the source location is represented relatively faithfully during the early portion of a sound, but this representation becomes increasingly degraded later in the stimulus. We show that the directional sensitivity of single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
59
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 87 publications
10
59
0
Order By: Relevance
“…Information transfer measures the extent to which stimulus azimuth is unambiguously encoded by spike count and is sensitive to both mean rate as well as trial-to-trial variability. Consistent with previous observations in anesthetized cat IC (Devore et al, 2009), we found that information transfer is highly correlated with the absolute range of firing rates across azimuth (data not shown, r 2 =0.83, p<0.001). Because we did not obtain enough stimulus trials to reliably estimate information transfer in many of the present units, we use the absolute range of firing rates to quantify directional sensitivity.…”
Section: Characterization Of Directional Sensitivity Using Itd-only Isupporting
confidence: 92%
See 3 more Smart Citations
“…Information transfer measures the extent to which stimulus azimuth is unambiguously encoded by spike count and is sensitive to both mean rate as well as trial-to-trial variability. Consistent with previous observations in anesthetized cat IC (Devore et al, 2009), we found that information transfer is highly correlated with the absolute range of firing rates across azimuth (data not shown, r 2 =0.83, p<0.001). Because we did not obtain enough stimulus trials to reliably estimate information transfer in many of the present units, we use the absolute range of firing rates to quantify directional sensitivity.…”
Section: Characterization Of Directional Sensitivity Using Itd-only Isupporting
confidence: 92%
“…In a reverberant sound field, reflected acoustic waves reach the listener from all directions, interfering with the direct sound and distorting the binaural cues for sound localization such as interaural time and level differences (ITD and ILD). In previous work (Devore et al, 2009), we showed that reverberation degrades the directional sensitivity of low frequency, ITD-sensitive neurons in the inferior colliculus (IC) of anesthetized cats, although not as much as predicted by an interaural crosscorrelation model. Here, we extend this work by characterizing directional sensitivity in neurons across a wide range of the tonotopic axis in an awake rabbit preparation, while maintaining our focus on neurons that are sensitive to ITD.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Listeners have a remarkable ability to localize sounds accurately in reverberant settings, a feat attributed to the fact that they give greater perceptual weight to location cues at sound onsets, suppressing cues from later-arriving reflections (Zurek 1980;Freyman et al 1997;Devore et al 2009). This "precedence effect" (PE;Wallach et al 1949) has been studied using a range of paradigms whereby a pair of dichotic clicks is presented with a brief inter-stimulus delay (ISD).…”
Section: Introductionmentioning
confidence: 99%